School segregation in public and semiprivate primary schools in Andalusia. - Prieto-Latorre, Claudia; Marcenaro-Gutiérrez, Óscar David; Vignoles, Anna (Taylor & Francis, 2020)
School segregation by socio-economic background is a feature of most education systems and impacts negatively on educational outcomes for poor children. Evidence on this issue is lacking for the Spanish primary education system and in particular the extent to which a) poor and rich students sort into different types of school and b) the extent of segregation within different school types. We measure the level of segregation of students from different socioeconomic backgrounds into public and semiprivate schools and within these two types of school using the Hutchens Index. The analysis is based on data for students attending 5th grade in the largest region in Spain (Andalusia). Our results indicate significant differences in the level of segregation across and within both school types. Students from higher socioeconomic backgrounds are more likely to attend semiprivate schools. This provides evidence of the inequity of providing public funding for semiprivate schools that are then disproportionately attended by wealthier students.
https://openpolicyfinder.jisc.ac.uk/id/publication/6831
Keywords: Discriminación en la enseñanza - Andalucía; School segregation; Socioeconomic level; Public schools; Semiprivate schools